Examining collective creative self-efficacy as a competency indicator of group talent management: a study of SMEs in an emerging economy. Issue 6 (26th March 2023) - Ghosh, Vinit; Sengupta, Tuhin; Narayanamurthy, Gopalakrishnan; Ishizaka, Alessio
Abstract: In this article, we examine how collective creative self-efficacy (CCSE) of a team can act as a competency indicator for team creativity output (TCO) in knowledge-intensive SMEs. As a team's creative efficacy shape the collective mental model about its social context, team climate of creativity is considered as a mediator in the relationship between CCSE and TCO. Through faultline-strength analysis, we investigate how team members' compositional attributes (age and job tenure) moderate the relationship between CCSE and team climate. A High sub-group separation (age and job tenure attributes) of team members is beneficial in a high CCSE team, whereas a homogeneity in age and tenure is desirable when a team's CCSE is low. Our results show group faultline-strength can significantly strengthen or dampen the existing team climate and team creativity output within SMEs, thus creating a strong basis for firm owners or managers to align teams for improved team output. Moreover, HRs in such firms can design interventions to measure and enhance teams'collective creative self-efficacy of a team that serve two purposes—a) act as a competency indicator that guides a team to become self-directed, and, b) strengthen the team creativity climate for producing creative deliverables.